Działania w procesie restrukturyzacji finansowej przedsiębiorstwa w kryzysie - Porada-Rochoń, Małgorzata (The Activities in Financial Restructuring Process of an Enterprise in Crisis, 2008)
At present, changing environment causes that enterprises are exposed to functioning in conditions of permanent crises. Restructuring (also financial restructuring) is one of the many solutions within anticipation of crisis. As a result of correctly planned and implemented operations, within the confines of financial restructuring, an enterprise does not only have a chance to survive but also a chance to develop in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 451-457